Problems and Prospects of Nayaka Community – A Sociological Study: Exploring the Social Dynamics and Development Strategies of the Nayaka Community in Karnataka (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The South Indian state of Karnataka, once princely states is rich in its Historic, Cultural and Anthropological Heritage. The Tribal Nayaka people represent only 6.95 of the population of the Karnataka state. There are as many as 51 Tribes notified by the Government of India living in Karnataka Extreme poverty and negligence over generations among the Nayakas has left them in poor state of health and nutrition. The Literacy rate is consistently lower than that of total population. Since recent years there is a demand among the Nayakas to increase the reservation to 7.5 in education and jobs. When extra reservation is given to the under privileged people other caste people will suffer. The reservation system in our country is not perfect. It won’t change until caste and religion section is taken off from official documents. We should not fight in the name of caste and religion, system will automatically change. There have been relatively more changes in Occupational structure from traditional occupation in this community. More over in the last decade or two Nayaka Community is emerging as a numerically significant group and is gaining important space in economic and social sphere. When caste inequalities end, then reservation among the Nayakas can be a tool for development.